Pengaruh Budaya Politik Terhadap Perilaku Politik Masyarakat Menjelang Pemilu 2024 Di Kecamatan Percut Sei Tuan - Saparutdin Brutu, Latifah hanum Gultom, Johana Adriani Nainggolan Desy yolanda Bangun, Enjelina Sina (Mediation : Journal Of Law, 2023)
This study aims to determine the influence of political culture on people's political behavior in the upcoming 2024 elections in Percut Sei Tuan District. The results of the study show that the majority of people in Percut Sei Tuan District have a participatory political culture that is supported by high political awareness. However, several factors such as education, mass media, family, and religion have an impact on people's political behavior. Political parties also play an important role in influencing people's political behavior, particularly in disseminating information and conducting political campaigns. Therefore, efforts are needed to increase the participation and political awareness of the people in Percut Sei Tuan District, especially through education and effective political campaigns. The government and educational institutions prioritize political education and increase public knowledge about the political process and their political rights. Political parties must comply with ethical standards and avoid unethical practices in carrying out effective and transparent political campaigns to increase public participation in the political process. The government must ensure the accessibility of elections for all citizens, especially for people with disabilities or who live in remote areas, as well as ensure visibility and findability in the electoral process. Communities in Percut Sei Tuan District should be encouraged to actively participate in the political process and the upcoming 2024 elections through public discussion forums and participatory programs.